Utility of Perioperative Measurement of Cell-Free DNA and Circulating Tumor DNA in Informing the Prognosis of GI Cancers: A Systematic Review. (21st February 2022) - Hsu, Phillip J.; Singh, Khushboo; Dhiman, Ankit; Witmer, Hunter D. D.; He, Chuan; Eng, Oliver S.; Catenacci, Daniel V. T.; Posner, Mitchell C.; Turaga, Kiran K.
Abstract : PURPOSE: Current surveillance imaging and tumor markers lack sensitivity for the early detection of recurrence in GI cancers. This study critically evaluates the current literature on the role of sequential measurement of circulating tumor DNA (ctDNA) before and after curative resection in informing recurrence. METHODS: A systematic search using a predefined, registered protocol was conducted for studies published between January 2010 and May 2020. Included studies described patients with GI cancers treated with curative-intent surgical resection and measurement of ctDNA both before and after surgery. Patients were divided into three groups on the basis of the presence or absence of ctDNA at these time points. The primary outcome was recurrence-free survival (RFS). RESULTS: The search yielded 3, 873 articles; five met the inclusion criteria and collectively evaluated 57 patients. Pooled median RFS was 62 months (interquartile range 19 to not reached). Although median RFS was not reached in group 1 (– to –) or group 2 (+ to –), median RFS in group 3 (+ to +) was 15 months (interquartile range 9.6-60.4 months). Cox hazard ratio was 4.46 (95% CI, 1.17 to 16.99; P = .028) between group 1 and group 2, and 10.47 (95% CI, 2.91 to 37.74; P < .001) between group 2 and group 3. CONCLUSION: Detectable ctDNA, either preoperatively or postoperatively, and its persistence after curative surgery are associated with a greater risk of recurrence and decreased RFS in GI cancers. Thus, perioperative measurement of ctDNA may be a useful postoperative risk stratification tool and guide additional therapies.